Fostering Islamic Education: Embracing Multicultural Islamic Religious Education Values - Qornain, Dzul; Sugiono, Sugiono; Hakim, Lukman; Rizquha, Ach (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This study aims to discuss the development of Islamic education by implementing the values of multicultural Islamic Religious Education in Madrasah. In order to obtain data from research results, research was carried out with a qualitative approach and this type of case study research. This research was conducted at MI Ihyaul Islam Pajarakan. Data collection techniques with participant observation, in-depth interviews, and documentation. The data collection technique uses the snowball sampling technique. The data sources used are primary and secondary. At the same time, the data analysis technique uses the Miles and Huberman model. The results of this study indicate that multicultural Islamic education is a response to the development of population diversity in Islamic educational institutions themselves, as well as demands for equal rights for each group. In broad terms, all students, regardless of their groups, such as gender, ethnicity, race, culture, social and religious strata, have the right to receive the same education. The implementation of the values of multicultural Islamic Religious Education in the development of Islamic educational institutions includes institutional aspects, curriculum aspects, and workforce aspects.